ApoB/ApoA1 ratio and subclinical atherosclerosis - Panayiotou, Andrie G.; Griffin, Maura; Georgiou, Niki; Bond, Dawn; Tyllis, Theodosis; Tziakouri-Shiakalli, Chrysa; Nicolaides, Andrew; Fessas, Charis (My University, 2008)
Aim. It has been demonstrated that an increased apolipoprotein B (ApoB)/apolipoprotein A-I (ApoA1) ratio is associated with atherogenic low density lipoprotein (LDL) particles and the development of clinical cardiovascular disease. The aim of this study was to test the hypothesis that ApoB/ApoA1 ratio is associated with early subclinical atherosclerosis as demonstrated by ultrasonic measurements. Methods. Both common carotid and common femoral bifurcations have been scanned with high-resolution ultrasound in 767 volunteers over the age of 40. The latter consisted of 95% of the population of two randomly selected areas. IMTcc, IMTmax (including plaques), total plaque thickness (TPT) (the sum of the thickest plaques present at each bifurcation in cm) and black plaque burden (BPB) (TPT means plaque type) using the Widder classification with type 1 being the most hyperechoic and calcified and type 5 the most hypoechoic plaque were recorded. A medical history was taken with emphasis on risk factors present and a fasting lipid profile including ApoB and ApoA1 was determined. Results. In the total population (N.=767) the mean (±SD) ApoB/ApoA1 ratio was 0.85 (±0.22). In linear regression analysis, the Apob/ApoA1 ratio was significantly associated with all the ultrasonic measurements of early atherosclerosis (intima media thickness, IMTcc, IMTmax, TPT and BPB). These findings remained significant after correcting for age, gender, smoking, hypertension and diabetes (P<0.001 for all). Conclusion. The results indicate that a high ApoB/ApoA1 ratio is associated not only with early atherosclerosis but also with hypoechoic (BPB) and by inference unstable plaques.
Keywords: Apolipoprotein B (ApoB); Apolipoprotein A-I (ApoA1); Low density lipoprotein (LDL); ApoB/ApoA1 ratio; Atherosclerosis